2009
DOI: 10.1080/10803548.2009.11076821
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Shoulder Postures and Moments of Force Among Different Skill Levels in the Wool Harvesting Industry

Abstract: The wool harvesting industry employs workers of varying skill levels that differ in both qualityperformance ergonomics sheep shearing biomechanics shoulder skill posture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…There has been very little research on the injury risk or biomechanical, ergonomic or physiological demands of wool handlers (Gregory et al 2009). Workplace observation ( Figure 1) reveals a predominantly female workforce working in a variety of repetitive postures (often stooped) picking up in excess of 200 fleeces per day, each weighing between 5 to 10kg, and "throwing" these onto wool sorting tables where they are prepared, graded, and separated into various quality components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been very little research on the injury risk or biomechanical, ergonomic or physiological demands of wool handlers (Gregory et al 2009). Workplace observation ( Figure 1) reveals a predominantly female workforce working in a variety of repetitive postures (often stooped) picking up in excess of 200 fleeces per day, each weighing between 5 to 10kg, and "throwing" these onto wool sorting tables where they are prepared, graded, and separated into various quality components.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace observation ( Figure 1) reveals a predominantly female workforce working in a variety of repetitive postures (often stooped) picking up in excess of 200 fleeces per day, each weighing between 5 to 10kg, and "throwing" these onto wool sorting tables where they are prepared, graded, and separated into various quality components. Gregory et al (2009) has recently investigated shoulder postures and loads of wool handlers and observed that highest skill (open class) spends significantly more time in neutral or mild shoulder postures. They suggest that risk of sustaining injury to the upper limb of the open class wool handler may be less than that of other skill levels and argue the potential importance of this observation for industry workforce training.…”
Section: Introductionmentioning
confidence: 99%